Campus Life in Contemporary Polish, Slovak, and Ukrainian Fiction - Blashkiv, Oksana (Respectus Philologicus, 2024)
The article focuses on the image of campus life as presented in a selection of novels written in Polish, Slovak, and Ukrainian after 1989. The author presents generic peculiarities of Slavic campus fiction and analyses the theme of (academic) coming-of-age in Slavic campus fiction. The maturation of student characters in Maryna Hrymych’s Yura and Pavol Parkov’s The Legend About the Language occurred in Soviet Ukraine and Czechoslovakia, respectively, around 1968. In contrast, the protagonists of Jagoda Grudzień’s Erasmopeja and Tania Kalytenko’s Antero undergo academic identity formation in contemporary Scandinavian countries as participants in academic exchange programs. While Hrymych and Rankov portray characters navigating totalitarian societies of the past, Grudzień and Kalytenko situate their students within the anxieties of the globalised world, where remembering the past remains crucial. The author concludes that contemporary campus fiction written in Slavic languages addresses the issues significant for the cultural memory of the particular nation. Collectively, these novels contribute to a sense of continuity in academic culture within East-Central Europe.
Keywords: student; university; history; campus novel; image of campus life